ELAEOCARPUS SERRATUS L. EXHIBITS POTENTIAL ANALGESIC AND ANTIDIARRHEAL ACTIVITIES IN MICE MODEL - Pinkey, A. A. H.; Khan, Z. I.; Taher, M. A.; Soma, M. A. (International Journal of Medicine and Medical Research, 2021)
Background. Elaeocarpus serratus L. (Family: Elaeocarpaceae) is a tropical fruit tree, traditionally used in the treatments of poisoning, diarrhea, arthritis, and other diseases. Objectives. The current study was performed to conduct the analgesic, antidiarrheal, and hypoglycemic activity of E. serratus in mice model using methanolic bark crude extract. Methods. To assess the peripheral and central analgesic activity, the acetic acid-induced writhing and tail immersion methods were respectively used. The castor-oil mediated antidiarrheal method was used to assess the antidiarrheal activity whereas, the tail tipping technique was conducted to determine the hypoglycemic activity of the plant extract. Results. In the peripheral analgesic assay, the methanolic bark crude extract of E. serratus significantly inhibits the number of writing 69.77% (200 mg/kg) and 73.26% (400 mg/kg) respectively (p<0.05) which was strongly comparable with standard NSAID drug diclofenac sodium 75.58% (p<0.05). Similarly, it shown a significant tail flicking response for 30 minutes, 60 minutes and 90 minutes of central analgesic activity assay. In antidiarrheal activity assay, the E. serratus substantially reduced the number of diarrheal feces 64.26% (200 mg/kg, p<0.05) and 78.57% (400 mg/kg, p<0.05) which was also comparable with the positive control loperamide. The hypoglycemic activity of E. serratus extract was not convincing. Conclusions. Our investigation demonstrated the significant analgesic and antidiarrheal activities of methanolic bark extract of E. serratus (200 and 400 mg/kg) in mice model.